Multibeam Echo Sounders-IMU Automatic Boresight Calibration on Natural Surfaces. Issue 2 (4th May 2017) - Seube, Nicolas; Keyetieu, Rabine
ABSTRACT: This paper details a new boresight calibration method for multibeam echo sounder systems This method is based on an automatic data selection algorithm, followed by a boresight least squares adjustment This method, called MIBAC (MultiBeam-IMU Boresight Automatic Calibration), takes in input overlapping survey strips following a simple line pattern over a regular slope. We first construct a boresight error observability criterion, used to select automatically the most sensitive soundings to boresight errors. From these soundings, we perform a 3D adjustment of the boresight angle, thus taking into account the coupling between angles. From a statistical analysis of the adjustment results, we derive the boresight angle precision. Numerical results obtained with four different multibeam echo sounder systems are presented and compared to those of a patch test calibration method. Finally, we demonstrate the performances of MIBAC through a standard deviation along the surface normal approach computed by principal component analysis.